Influence of previous experience with and beliefs regarding anal cancer screening on willingness to be screened among men living with HIV - Jennifer L. Gillis; Troy Grennan; Ramandip Grewal; Gina Ogilvie; Mark Gaspar; Daniel Grace; Aisha Lofters; Janet M. Raboud; Olli Saarela; Paul MacPherson; Ron Rosenes; Irving E. Salit; et al. (BMC Public Health, 2022)
Abstract Background Implementation of anal cancer screening requires the procedure to be acceptable to the target population. Our objective was to assess the beliefs of men living with HIV regarding anal cancer screening and identify factors associated with their willingness to participate in screening. Methods We developed a cross-sectional questionnaire using the Theory of Planned Behavior to examine beliefs regarding prevention of human papillomavirus (HPV)-related diseases, administered to men living with HIV in 2016–2017 in a multi-site HIV clinical cohort. Correspondence analysis was used to examine the interrelationships between men’s beliefs and willingness to undergo anal cancer screening. We used multivariable proportional odds models to identify factors associated with increasing willingness. Results were reported as adjusted odds ratios (aOR) with 95% confidence intervals (CI). Results Among 1677 male participants, the vast majority (90%) would be willing to undergo screening by “anal Pap test”; willingness clustered with positive beliefs (e.g. confident they can get screened; disagree that they will feel pain) in the correspondence analysis. Higher self-perceived risk for anal cancer and positive beliefs regarding screening were associated with higher willingness to be screened. Gay, bisexual and other men who have sex with men had higher willingness (aOR = 1.62; 95% CI: 1.15, 2.29) than heterosexual men. Racialized men reported lower willingness (aOR = 0.68; 95% CI: 0.54, 0.89) than white men. Conclusions Men generally had positive beliefs and were willing to undergo screening, though there were differences by sexual orientation and racial identity. Tailored community-led initiatives could focus on men’s understanding of their risk and expectations of anal cancer screening to facilitate participation.